Influence of age and gender specifics of social network users in Russia on marketing and advertising methods - L. G. Akhmaeva (Цифровая социология)
A brief overview of the history of the Internet and social networks in the world and in Russia in particular has been provided. The concepts of social network, user profile and properties inherent in any social network – virtuality, interactivity and multimedia have been сharacterized and revealed. Dynamic data on the state of digital technologies for 2019 in the world and in Russia in particular have been analysed. The history and prospects for further development of social networks have been considered. Statistical data on the number of users of the 9 most popular social networks in Russia, namely: their activity, the amount of time spent on the Internet and in social networks, age and gender specifics and preferences of the technical devices used and types of Internet connection have been adduced. General recommendations to marketers on accurate targeting of ads placed in social networks have been given. To do this, companies should work with groups of users, that are united by a number of parameters, as well as create communities in social networks by companies that convey new information to users. Using data on the age, gender and other attributes of the target audience of social networks, marketers will be able to successfully solve the problems of increasing brand awareness and loyalty, attracting new customers, influencing the search promotion of external resources (sites and communities) containing information about the brand, products and services, and using them as effective tools for attracting potential customers.